Survey of Trogoderma spp. in Spanish mills and warehouses. (September 2020) - Castañé, Cristina; Agustí, Nuria; Estal, Pedro del; Riudavets, Jordi
Abstract: The distribution of Trogoderma granarium Everts has expanded steadily in recent years. This is a very destructive coleopteran species with many economic implications for the trade of grains in countries where it is present. Therefore, it is important to gather data that can confirm or reject the pest's establishment in a particular country. Spain has been cited as a location where the species is established; however, the present study demonstrates that no actual data support its stablishment in Spain. We surveyed fifteen storage premises (mills and warehouses for animal feed, wheat, and rice) distributed along the Iberian Peninsula over two years. We used traps baited with Trogoderma spp . sex pheromone to conduct the survey. Collected samples were morphologically and molecularly identified, since the morphological identification of this species is difficult. Although we found populations of T. inclusum in most of the sampled premises, and even T. variabile in one of them, no T. granarium was found in any of them. Abundant samples of other coleopterans were captured in the traps, including Oryzaephilus surinamensis, Tribolium spp., Sitophilus spp., Cryptolestes ferrugineus, Lasioderma serricorne and Rhyzopertha dominica . In conclusion, no T. granarium was found in our samplings in Spain. Highlights: T. granarium is a very destructive species with significant economic implications. It is reported to be established in Spain, but no recent data support this. A two-year survey was conducted in 15 storage premises in east and south Spain. Samples were morphologically and molecularly identified to avoid misidentifications. No T. granarium was found suggesting that, at most, is sporadically present.